Radioecological reliability of slope ecosystem - I. V. Matveeva (Ядерна фізика та енергетика)
Natural and technogenic cataclysms taking place in Ukraine bring to the forefront the problem of estimation and forecast of different ecosystems type. Theory and models of the radio capacity and reliability developed by us allow to describe adequately regularities of radionuclide migration and redistribution in slope ecosystems, and carry out mathematical modeling of investigated phenomena. That will give the possibility to use special coun-termeasures.